The Financial Instability Hypothesis - Hyman P. Minsky (Levy Economics Institute of Bard College, 1992)
The Financial Instability Hypothesis (FIH) has both empirical and theoretical aspects that challenge the classic precepts of Smith and Walras, who implied that the economy can be best understood by assuming that it is constantly an equilibrium-seeking and sustaining system. The theoretical argument of the FIH emerges from the characterization of the economy as a capitalist economy with extensive capital assets and a sophisticated financial system. In spite of the complexity of financial relations, the key determinant of system behavior remains the level of profits: the FIH incorporates a view in which aggregate demand determines profits. Hence, aggregate profits equal aggregate investment plus the government deficit. The FIH, therefore, considers the impact of debt on system behavior and also includes the manner in which debt is validated. Minsky identifies hedge, speculative, and Ponzi finance as distinct income-debt relations for economic units. He asserts that if hedge financing dominates, then the economy may well be an equilibrium-seeking and containing system: conversely, the greater the weight of speculative and Ponzi finance, the greater the likelihood that the economy is a "deviation-amplifying" system. Thus, the FIH suggests that over periods of prolonged prosperity, capitalist economies tend to move from a financial structure dominated by hedge finance (stable) to a structure that increasingly emphasizes speculative and Ponzi finance (unstable). The FIH is a model of a capitalist economy that does not rely on exogenous shocks to generate business cycles of varying severity: business cycles of history are compounded out of (i) the internal dynamics of capitalist economies, and (ii) the system of interventions and regulations that are designed to keep the economy operating within reasonable bounds.
Keywords: 330